Effect of the difference in spectral outputs of the single and dual-peak LEDs on the microhardness and the color stability of resin composites - Hye-Jung Park; Sung-Ae Son; Bock Hur; Hyeon-Cheol Kim; Yong-Hoon Kwon; Jeong-Kil Park (Korean Academy of Conservative Dentistry, 2011)
Objectives To determine the effect of the spectral output of single and dual-peak light emitting diode (LED) curing lights on the microhardness and color stability of commercial resin composites formulated with camphorquinone and alternative photoinitiators in combination. Materials and Methods Three light-polymerized resin composites (Z100 (3M ESPE), Tetric Ceram (Ivoclar Vivadent) and Aelite LS Posterior (Bisco)) with different photoinitiator systems were used. The resin composites were packed into a Teflon mold (8 mm diameter and 2 mm thickness) on a cover glass. After packing the composites, they were light cured with single-peak and dual-peak LEDs. The Knoop microhardness (KHN) and color difference (ΔE) for 30 days were measured. The data was analyzed statistically using a student's t-test (p < 0.05). Results All resin composites showed improved microhardness when a third-generation dual-peak LED light was used. The color stability was also higher for all resin composites with dual-peak LEDs. However, there was a significant difference only for Aelite LS Posterior. Conclusions The dual-peak LEDs have a beneficial effect on the microhardness and color stability of resin composites formulated with a combination of camphorquinone and alternative photoinitiators.